ANALISIS FILOSOFIS TERHADAP PERAN HEREDITAS, LINGKUNGAN, KEBEBASAN MANUSIA, DAN HIDAYAH ALLAH DALAM MEMBENTUK KARAKTER ISLAMI - Firmansyah Firman; Nur Afifah (El-Ihsan: Journal of Contemporary Islamic Education, 2026)
Human behavior is complex and can easily be influenced by various factors, including heredity, environment, human freedom, and belief in the existence of guidance from Allah.This research aims to analyze the role of heredity, environment, human freedom, and Allah guidance in shaping Islamic character. This research uses a "library research" method and an Islamic educational philosophy approach. Data analysis is conducted descriptively by reviewing various related literature to understand the role of heredity, environment, human freedom, and Allah guidance in shaping Islamic character. The research results indicate that the elements that have an impact on the process of forming a person's personality come from internal factors, namely heredity (heredity), and external factors, namely the environment and human freedom. These three factors can be said to be interrelated within the framework of guidance and guidance from Allah. Therefore, it cannot be denied that guidance from Allah can shape a person's personality. Guidance is not only in the form of guidance, but also in the form of advice and enlightenment that comes through religious guidance, guidance of reason or the heart, guidance of the mind, and guidance of the five senses.